Short-term digital ocular massage may weaken corneal biomechanics - Lam, Andrew K. C.; Lee, Sandy N. S.; Mui, Mason W. S.; Ng, Venus H. Y. (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeDigital ocular massage has been demonstrated to reduce intraocular pressure (IOP). However, its influence on corneal biomechanics remains unclear. In this study, a device employing Corneal Visualization Scheimpflug Technology (Corvis ST) was used to monitor changes in IOP and corneal biomechanics following short-term digital ocular massage in low and high myopes.MethodsIn total, 29 low myopes and 29 high myopes participated in this study. The right eyes (treatment eyes) underwent digital ocular massage for 5 min, whereas the left eyes (control eyes) remained closed during the procedure. Biomechanically-corrected IOP (bIOP) was measured in both eyes by using Corvis ST at three time points: before the ocular massage, immediately after the ocular massage, and 15 min post-massage. Dynamic corneal response (DCR) parameters were also monitored, namely, peak distance (PeakDist), highest concavity time (HCT), deformation amplitude (DA), deflection amplitude (DefleA), stress-strain index (SSI), time taken to reach the second applanation (A2T), and velocity required to reach the second applanation (A2V).ResultsAt baseline, the participants exhibited comparable bIOP in both eyes. A significant reduction in bIOP was observed in the treatment eyes immediately after ocular massage (low myopes: 16.15 ± 2.79 vs. 14.82 ± 3.20 mmHg, p < 0.05; high myopes: 16.81 ± 1.51 vs. 15.39 ± 1.70 mmHg, p < 0.05). Corneal biomechanics at baseline were comparable between the treatment and control eyes. High myopes exhibited more deformable corneas, characterized by a shorter HCT (treatment eyes: 17.30 ± 0.41 vs. 17.72 ± 0.30 msec, p < 0.001; control eyes: 17.33 ± 0.32 vs. 17.55 ± 0.44 msec, p = 0.023), and lower SSI (treatment eyes: 0.739 ± 0.100 vs. 0.848 ± 0.114, p < 0.001; control eyes: 0.741 ± 0.103 vs. 0.858 ± 0.112, p < 0.001) than low myopes at baseline. Immediately after ocular massage, the treatment eyes in both groups exhibited shorter A2T, higher A2V, larger PeakDist, and higher DA and DefleA. Corneal biomechanics in the control eyes remained stable throughout. All DCR parameters returned to baseline levels 15 min after the ocular massage.ConclusionShort-term digital ocular massage results in a temporary reduction in bIOP. The observed changes, including shorter A2T, higher A2V, larger PeakDist, and greater DA and DefleA indicated a greater corneal deformability after ocular massage. These findings support the potential association between eye rubbing and the etiology or progression of keratoconus.